The Impact of COVID-19 on Transportation of Adults With Visual Impairments. (November 2022) - Zebehazy, Kim T.; Rosenblum, L. Penny; Thompson, Kathleen M.
Introduction: Access to efficient and affordable transportation options has long been a challenge for many individuals with vision loss. In spring 2020, the COVID-19 pandemic caused a quick shift in the availability and safety of transportation.Methods: Using the constant comparison method, open-ended responses from 1, 162 participants in the Flatten Inaccessibility study were coded. Responses were from participants who had concerns about transportation.Results: Ten themes and corresponding subthemes emerged from the data. Themes were interdependent in that the extent of concerns differed based on respondents' support networks, transportation availability, and financial circumstances.Discussion: The COVID-19 pandemic brought to the forefront both systemic and COVID-19 transportation challenges about which those with visual impairments experienced or had concerns or both.Implications for Practitioners: It is imperative that professionals support those with visual impairments to develop alternative plans for when their typical transportation options are disrupted.